A Mechanism of Hot-spots Formation at the Crack Tip of Al-PTFE under Quasi-static Compression - Feng, B.; Li, Y.; Hao, Hong; Wang, H.; Hao, Yifei; Fang, X. (2017)
© 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. Generally, the Al-PTFE (polytetrafluoroethylene) is thought to be inert under quasi-static or static loads. However, it was found that Al-PTFE would initiate under quasi-static compression after a specific heat treatment procedure and the opening fracture plays a crucial role in the initiation. A unique micrographic fracture pattern which showed unstable crack propagation and a ductile-to-brittle transition was observed at openning cracks by SEM. Combining the observed microstructure with the stress distribution at the path of crack propagation derived from numerical simulation, a mechanism was proposed to explain the formation of “hot-spots” at the crack tip. The temperature rise at the crack tip was estimated to be at least 612 °C, which is high enough to ignite the Al-PTFE composite.